Contemporary Nonpharmacological Strategies to Manage Preoperative Anxiety: Nonsystematic Review - Vilma Kuzminskaitė; Agnė Ramaškaitė; Justina Semenkovaitė; Eglė Kontrimavičiūtė (Acta Medica Lituanica)
Background: Preoperative anxiety affects the majority of surgical patients and has a huge impact on their well-being and recovery. Pharmacological anxiety treatment does not always result in the desired effect and occasionally causes side effects. To address this issue, recent research is focused on inventing and studying nonpharmacological anxiety management techniques.Objectives: To review the diversity of recent nonpharmacological anxiety-reducing methods for adult and pediatric patients and compare their effectiveness and applicability in real-life clinical practice.Methods: The search was performed using keywords ‘preoperative anxiety’, ‘management techniques’, ‘nonpharmacological’, ‘pediatric’ in PubMed and Google Scholar databases. Full-text original articles or reviews that were published during the last 5 years were selected. Anxiety management techniques were identified and further analyzed for advantages and disadvantages.Results: Patient education, educational videos and music seem to be the most effective and easy to implement in daily practice for adults. While playing rooms and interactive pop-up books are reasonable to manage preoperative anxiety for pediatric patients.Conclusions: The choice of nonpharmacological anxiety management methods is diverse. However, the availability and application in reality highly depend on numerous variables, such as costs, time availability, motivation of the medical team, cultural background, and preference of the patient.